Penerapan Sistem Absensi ID Card RFID Terhadap Perhitungan Honorarium, Kedisiplinan Pegawai dan Peningkatan Kualitas di Perguruan Darulfunun El-Abbasiyah - Donna Ramadhan Fitri; Sepryta Handayani; Ferdi Yufriadi; Mona Eliza; Abdullah A Afifi (IDRIS Darulfunun Institute, 2024)
This research discusses the implementation of the RFID ID Card attendance system in the context of salary management and teacher and employee discipline at Darulfunun El-Abbasiyah College. The main objective of this research is to identify how the application of RFID ID Card technology in an attendance system can influence salary management and the level of discipline among teachers and employees in an institution or organization. The research method used is a descriptive method with a case study approach, then analyzed qualitatively to describe the impact of implementing the RFID ID Card attendance system on salary management and discipline. The results of this research show that the implementation of the RFID ID Card attendance system has several significant impacts. First, in terms of salary management, this system allows more accurate salary calculations based on real absences, reduces calculation errors, and minimizes the potential for system abuse. Second, regarding discipline, this system tends to increase the discipline of teachers and employees because their attendance is recorded accurately. This can also reduce the tendency to be late or absent from work for no apparent reason. Although implementing an RFID ID Card attendance system provides various benefits, this research also identified several challenges. The main challenges include the need for adequate training for system users, regular maintenance of RFID ID Card technology, and the importance of maintaining the privacy and security of user data. Overall, this research concludes that implementing an RFID ID Card attendance system can have a positive impact on salary management, discipline of employees, and quality improvement. However, successful implementation depends on a good understanding of this technology, adequate training, and appropriate actions to overcome challenges that may arise.